EMPOWER-PD - A physical therapy intervention to empower the individuals with Parkinson's disease: A study protocol for a feasibility randomized controlled trial - De Oliveira Braga H.* (2019)
© The Author(s).Background: One of the greatest barriers found by physical therapy treating individuals with Parkinson's disease (PD) is the adherence to treatment, associated with the lack of motivation to remain active. Therefore, there is a need to change the look given to physical therapy and for the individual, seeking the centralization of the therapy in their preferences. This study aims to present the EMPOWER-PD, a protocol based on individual preferences and its design for feasibility. Method: A 12-week pilot for a randomized clinical trial will assess the feasibility and preliminary effectiveness of the EMPOWER-PD and make comparisons with conventional physical therapy (CPh). Both protocols consist of mobility and locomotion training, and aim at improving motor and non-motor symptoms through different approaches. The EMPOWER-PD aims to provide a source of motivation and empowerment of health through the self-knowledge of the individual's abilities and limitations, in a protocol that addresses individual preferences. The CPh is based only on physiotherapist decisions, not addressing the individual's preferences or motivation/empowerment. The target recruitment will be 24 PD individuals, between stages I and III of Hoehn and Yahr (HY), who will be recruited from Brazilian Parkinson's disease Rehabilitation Initiative (BPaRkI) with allocation ratio 1:1. A computerized block randomization procedure will be implemented by a blinded researcher with the participants blinded to group assignment. The sessions will be conducted in a group setting, twice a week, during 60 min for 8 weeks, followed by 4 weeks of follow-up. The primary outcomes will be the feasibility data (adherence, recruitment rate, and safety). The secondary outcomes will assess the preliminary efficacy on qualitative assessment about individual's motivation/empowerment and quantitative motor outcomes (Timed Up and Go and Dynamic Gait Index) and non-motor symptoms (6-min walk test and Fatigue Severity Scale). The recommendation to have 6-12 participants per group will be adopted based on the qualitative analysis to the sample size. Discussion: This study will provide important insights about the physical therapy approach in PD individuals. The EMPOWER-PD is innovative because (1) it proposes an intervention that includes an individual-centered approach with motor control principles; (2) it aims to provide a source of motivation and empowerment of health; (3) assesses the individual in a global view considering motor and non-motor symptoms, using both, qualitative and quantitative metrics.